2014
DOI: 10.1186/1471-2334-14-153
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and immunological outcomes according to adherence to first-line HAART in a urban and rural cohort of HIV-infected patients in Burkina Faso, West Africa

Abstract: BackgroundAim of our study is to investigate the clinical and immunological outcomes according to first-line HAART adherence in a large cohort of HIV-infected patients in Burkina Faso.MethodsA retrospective study was conducted between 2001 and 2009 among patients from two urban medical centers [St. Camille Medical Center (CMSC) and “Pietro Annigoni” Biomolecular Research Center (CERBA)] and 1 in the rural District of Nanoro (St. Camille District Hospital). Socio-demographical and clinical data were analyzed. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Poor adherence leads to clinical failure, resulting in poor CD4 count, giving rise to OIs, and thereby increasing the risk of mortality. Various studies conducted across the globe have reported that poor adherence to ART increases mortality [15,28,29]. The results from our study as well as from similar studies across the world have pointed towards a variety of factors which predict mortality among PLHIV.…”
Section: Discussionsupporting
confidence: 68%
“…Poor adherence leads to clinical failure, resulting in poor CD4 count, giving rise to OIs, and thereby increasing the risk of mortality. Various studies conducted across the globe have reported that poor adherence to ART increases mortality [15,28,29]. The results from our study as well as from similar studies across the world have pointed towards a variety of factors which predict mortality among PLHIV.…”
Section: Discussionsupporting
confidence: 68%
“…<75%) for patient retention on ART, translated into 40% potential lost to follow-up [12]. As loss to follow-up are known as possible HIVDR, national ART programs in SA has ~40% likelihood of experiencing HIVDR emergence in a short-medium run [10, 11]. Of note, only 10.71% ART clinics and only one region (Littoral) had acceptable performances (excellent or fair), suggesting that ~90% of ART clinics as well as 90% of regions are experiencing high risks of HIVDR due to poor retention on ART, similar to findings from other SSA-settings [13].…”
Section: Discussionmentioning
confidence: 99%
“…Retaining patients on lifelong ART, is an essential component in HIVDR prevention through adherence promotion, considerably improved the clinical and immunological outcomes [10, 11], reduced lost to follow-up and prolong the life expectancy of treated-patients [3]. As this indicator remains with uncertainty [79], it became crucial for the national AIDS programme to delineate the country performance in patient retention on ART as well as related determinants.…”
Section: Introductionmentioning
confidence: 99%
“…Another part of the present results confirm those of Palella et al [ 3 ], Nachega et al [ 7 ], and Abaasa et al [ 8 ] regarding the link between the average adherence and patient survival. Moreover, in a recent study conducted in Burkina Faso [ 25 ], the authors expressed adherence with a score (ranging from 0 to 10 points) and considered it in a Cox model as a time-varying covariate to point out that the less adherent patients had a higher risk of death. By classifying adherence into two categories (optimal: 8–10 points and sub-optimal: 0–7 points), the authors showed also that patients with optimal adherence had the best CD4-cell-count recovery.…”
Section: Discussionmentioning
confidence: 99%